Lorna Weatherill: Consumer Behaviour & Material Culture in Britain 1660-1760 & Lorna Weatherill, ed.: The Account Book of Richard Latham 1724–1767 - Jaine, Tom (Petits Propos Culinaires, 2014)
Lorna Weatherill: Consumer Behaviour & Material Culture in Britain 1660-1760: Routledge, 2nd edition 1996: 252 pp., paperback, £26.99.Lorna Weatherill, ed.: The Account Book of Richard Latham 1724–1767: Oxford University press for the British Academy (Records of Social and Economic History, new series xv), 1990: 284 pp., hardback, £65.00.